PERANCANGAN DAN IMPLEMENTASI LEMARI PENYIMPANAN ALAT PERMAINAN EDUKATIF DI TK INDRIYASANA, BABADAN, WEDOMARTANI, SLEMAN, DIY - V. Ariyono; Widagdo Purbowaskito (Universitas Sanata Dharma, 2018)
Kindergarten is an educational institution which plays an important role in building cognitive, affective, and psychomotor skills of pupils. Indriyasana Kindergarten Babadan is a school that uses educational game stuff as one of the learning media. It is required to continually maintain this educational game stuff including its storage in order to enhance this learning method. However, there is a problem faced by Indriyasana Kindergarten Babadan that is the school does not have cupboards to keep its educational game stuff. This community service program implements ergonomic scientific/field to design a cupboard to keep educational game stuff based on anthropometry of teachers in Indriyasana Kindergarten Babadan. The result of this program was to design three kinds of cupboards. They were cupboards with two sledding doors, cupboards with one hinge door, and cupboards without doors.